Initial Experience of Clinical Use of [99mTc]Tc-PSMA-T4 in Patients with Prostate Cancer. A Pilot Study - Jarosław B. Ćwikła (MDPI AG, 2021)
Numerous different molecules of prostate-specific membrane antigen (PSMA) ligands are used to detect prostate cancer (PCa); most approaches utilize gallium PET and a few reports describe the role of SPECT/CT. [99mTc]Tc-PSMA-T4 is a new radiopharmaceutical designed for the diagnosis of patients with PCa. We conducted a single site, prospective, preliminary case series study that included 31 patients with PCa; all had undergone clinical, biochemical or imaging examination and exhibited clear or suspicious active disease or clinical/biochemical recurrence of PCa. Whole-body (WB) SPECT/CT after i.v. administration of [99mTc]Tc-PSMA-T4 was utilized; acquisition images were obtained at three time points. The clinical value of the images was assessed in regard to the evaluation of tumor extent in patients with confirmed PC that qualified for initial therapy and the evaluation of tumor recurrence; both provided encouraging results. The late acquisition of WB-SPECT resulted in better lesions delineation. The results of the analysis of the sensitivity/specificity were: 92%/100% in cases of primary cancer, 83%/100% in terms of pelvic lymph nodes disease, 100%/95% in other lymph nodes and soft tissue involvement, respectively, and bone mets were both 100%. An oncotropic SPECT [99mTc]Tc-PSMA-T4 can help in selecting a rational therapeutic strategy for a patient with an initial diagnosis of PCa by assessing the extent of cancer and also after complex radical or palliative therapy in case of biochemical recurrence for re-staging.